Factors associated to medical consultations by elderly adults in southern Brazil: a population based study - Juliana Regina Destro; Antonio Fernando Boing; Eleonora d'Orsi (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To analyze the prevalence of medical consultations in the last three months among elderly adults and associated factors. Methods: A cross-sectional, population-based study was carried out with 1,705 elderly adults (60+ years of age) in the urban region of Florianópolis, Santa Catarina, Brazil, in 2009 and 2010. The sampling selection was performed in two stages. The sample was complex, with census tracts as primary and households as secondary sampling units. For association analysis, Poisson regression was performed using predisposing factors, enabling factors and need as independent variables, according to Andersen's theoretical model. Results: The response rate was 89.2%. The prevalence of medical appointments by elderly adults was 70.4% (95%CI 67.5 - 73.4). Factors associated with higher prevalence of medical consultations in the crude analysis were female gender, accumulation of chronic diseases, negative self-perception of health, and report of chronic pain. The multivariate analysis showed that having at least one chronic disease and negative self-perception of health was positively associated with the outcome. Conclusion: Only variables from the need dimension were associated with medical consultations, indicating an equal use of this service.